Utilizing Rasch Model to Analyze A Gender Gap in Students’ Scientific Literacy on Energy - Mardiah Afifa; Rini Khoirunnisa; Sri Mindia Vanessa Pratiwi; Dariah Meitaza (Jurnal Pendidikan Fisika Indonesia)
The purpose of this study was to analyze the gap in scientific literacy between male and female students in the subject of energy. This study involves junior high school students which differentiated by gender. The instruments used in this study were the 2006 and 2015 PISA tests, which consisted of nine questions and were analyzed using the Rasch model. The data was analyzed using the Wright map, person measure, item reliability, and DIF. The findings revealed no significant difference between male and female students' scientific literacy, even though male students' percentage results were more significant than female students. Therefore, this study shows no gender gap in students' scientific literacy in energy material. However, students have low literacy, with a logit of -0.51, so physics teachers must create teaching methods to improve students’ scientific literacy. This research is useful for providing information on the use of the Rasch analysis model to analyze gender gaps in students' scientific literacy, which has the potential to pave the way for the prevention of bias and the development of more effective strategies in achieving gender equality in science education.